2015
DOI: 10.1111/ajad.12159
|View full text |Cite
|
Sign up to set email alerts
|

Prescription medication misuse among opioid dependent patients seeking inpatient detoxification

Abstract: Background and Objectives: Opioid related morbidity and mortality is heightened in context to the concomitant use of psychotropic medications. The aim of this project was to examine the extent to which opioid dependent patients seeking detoxification are using and misusing specific psychotropic agents. Methods: As part of a quality assurance/improvement project, we systematically assessed prospectively consecutive admissions to a public detoxification program using a self-report questionnaire to query for spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 30 publications
2
30
0
3
Order By: Relevance
“…Euphoria is a documented side effect of pregabalin, and tolerance and withdrawal have been reported [14,15]. Populations thought to be at risk of pregabalin misuse include people with prior or ongoing substance abuse, particularly opioid abuse [16][17][18][19]. Populations thought to be at risk of pregabalin misuse include people with prior or ongoing substance abuse, particularly opioid abuse [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Euphoria is a documented side effect of pregabalin, and tolerance and withdrawal have been reported [14,15]. Populations thought to be at risk of pregabalin misuse include people with prior or ongoing substance abuse, particularly opioid abuse [16][17][18][19]. Populations thought to be at risk of pregabalin misuse include people with prior or ongoing substance abuse, particularly opioid abuse [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, pregabalin misuse among people with opioid use disorder is as high as 68% [20]. Several studies have also reported higher rates of gabapentinoid abuse among people with psychiatric diagnoses [4,17]. Several studies have also reported higher rates of gabapentinoid abuse among people with psychiatric diagnoses [4,17].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the other commonly prescribed medications— including antipsychotics, especially quetiapine (Reeves and Ladner, 2014), as well as tricyclic antidepressants (Seale et al, 2014)—have been reported to be used non-medically by patients receiving buprenorphine to enhance the euphoric effects of the opioid. Many medications that were commonly prescribed in our study—including clonazepam, clonidine, and gabapentin—are known to be misused by patients with OUD seeking detoxification (Wilens et al, 2015). These medications are sedating and could contribute to hypoventilation, hypoxia and accidental overdose, especially in combination with an opioid (Kotlinska-Lemieszek et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of the rising national prevalence of psychoactive polypharmacy among outpatient psychiatrists, other researchers note that many of these medication combinations are not evidence-based and come with increased risk and unknown clinical benefit (Mojtabai and Olfson, 2010). In patients with OUD, potential additional risks of polypharmacy exist such as de-stabilization of OUD recovery (Caviness et al, 2013; Heikman et al, 2016; Wilens et al, 2015). However, these risks must be balanced with the need to manage patients’ mood, sleep and pain symptoms to continue to keep them engaged in buprenorphine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Following marketing authorization, observational studies, case reports and meta-analyses of clinical trials have reported euphoria (200), dependence (102,201), tolerance development and dose increases (202)(203)(204), use of supra-therapeutic doses (205), withdrawal symptoms (206), substance-seeking behaviour (132,207), non-prescribed use and diversion (110,132,208), as well as intoxications, drug-related deaths (110,187), and drug-impaired driving (209). Of patients dispensing pregabalin, a small proportion of the users account for a large part of the total drug expenditure (200,210), which might indicate misuse and abuse (79).…”
Section: Pregabalinmentioning
confidence: 99%